MIXTURE TRACES PROBABILISTIC ANALYSIS IN THE COMPARISON OF SEVERAL HYPOTHESES - Andrade, Marina; Ferreira, Manuel Alberto M. (Acta Scientiae et Intellectus, 2024)
The objective of this work is to discuss various approaches in the analysis of DNA mixture profiles, starting with a mixture trace with only two contributors and extending the analysis to a larger number of contributors. Both the algebraic treatment and the use of OOBN are considered concluding with the inevitability of using the latter in more complex situations.